2021
DOI: 10.3390/s21072361
|View full text |Cite
|
Sign up to set email alerts
|

The Prediction of Body Mass Index from Negative Affectivity through Machine Learning: A Confirmatory Study

Abstract: This study investigates on the relationship between affect-related psychological variables and Body Mass Index (BMI). We have utilized a novel method based on machine learning (ML) algorithms that forecast unobserved BMI values based on psychological variables, like depression, as predictors. We have employed various machine learning algorithms, including gradient boosting and random forest, with psychological variables relative to 221 subjects to predict both the BMI values and the BMI status (normal, overwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…A wide range of ML-based algorithms incorporating various predictors and risk factors, training set sizes, and degrees of implementation have been used to predict adult obesity [11,14]. The reported accuracy of ML algorithms to predict adult obesity as a binary outcome ranges broadly, from 0.59 to 0.97 for overall accuracy [15][16][17][18][19][20][21][22][23][24] and 0.51 to 0.99 for the area under the curve (AUC) [15,19,20,23,24]. A review suggested that ML-based models predicted childhood and adolescent obesity much better than linear regression [13].…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of ML-based algorithms incorporating various predictors and risk factors, training set sizes, and degrees of implementation have been used to predict adult obesity [11,14]. The reported accuracy of ML algorithms to predict adult obesity as a binary outcome ranges broadly, from 0.59 to 0.97 for overall accuracy [15][16][17][18][19][20][21][22][23][24] and 0.51 to 0.99 for the area under the curve (AUC) [15,19,20,23,24]. A review suggested that ML-based models predicted childhood and adolescent obesity much better than linear regression [13].…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning (ML) algorithms have been used to forecast BMI values based on psychological variables, like depression, with an accuracy of over 80% ( Delnevo et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, of the 3090 articles identified initially through the keyword search, 46 (1.49%) were included in the review . [28,32,33,37,42,46,48,[50][51][52][53]57,58,60,62,63]; 6 (13%) in China [39,40,45,56,64,65]; 3 (7%) each in the United Kingdom [27,68,69] and Korea [35,43,49]; 2 (4%) each in Italy [36,71], Turkey [41,70], Finland [44,59], Germany [54,55], and India [36,71]; and 1 (2%) each in Saudi Arabia [26], Iran [67], Serbia [66], Portugal [61], Spain [47], Singapore [38], Australia [34], and Indonesia [29]. Of the 46 studies, 32 (70%) adopted a cross-sectional study design [26,…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…Of the 46 studies, 23 (50%) focused on adults, 14 (30%) on children and adolescents, 1 (2%) on people of all ages, and the remaining 8 (17%) did not report the age range of participants. [26][27][28][29][33][34][35][36][37]39,41,[44][45][46][47][49][50][51][53][54][55][56][58][59][60][61][62][63][64][65][66][67][68]70], 8 (17%) analyzed digital image data [30,31,38,40,42,43,57,71], and 4 (9%) analyzed text data [32,48,52,69]. Obesity-related measures used across the studies included anthropometrics (eg, body weight, BMI, BFP, WC, and WHR) and biomarkers.…”
Section: Identification Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation